Biological Evaluation of (2-(2-(2-Nitrophenyl) Diazinyl) Malononitrile): Focus on Antibacterial Activity - H. H. Nawar; Khaled Abdusalam B. A; Mohamed Ali Salem (African Journal of Advanced Pure and Applied Sciences, 2025)
The rise of multidrug-resistant (MDR) bacteria poses a significant challenge to the antibacterial efficacy of the produced chemical, (2-(2-(2-nitrophenyl) diazinyl) malononitrile), which is generated from malononitrile and a diazo moiety. The molecule was synthesized using the diazotization of 2-nitroaniline, followed by coupling with malononitrile, resulting in NPDAM with an 85% yield and a melting point of 123-125 °C. The substance at concentrations of 1, 5, and 10 mg/mL was assessed against methicillin-resistant Staphylococcus aureus (MRSA) (SA121) and Escherichia coli (EC49). The chemical exhibited efficacy against MRSA at varying doses, yielding clear zones of 29.6, 32.6, and 33.0 mm, in contrast to E. coli at the same concentrations, which produced clear zones of 10, 11.6, and 14.6 mm, respectively. The microdilution technique was employed to ascertain the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values. The compound exhibited low minimum inhibitory concentration (MIC) values against MRSA at concentrations of 1 and 5 mg/mL (19.5 and 4.89 µg/mL, respectively), in contrast to E. coli, which demonstrated inhibition at 39.0 and 9.78 µg/mL at the same concentrations. Additionally, it yielded the lowest MIC values (0.97 µg/mL) against both bacteria at a concentration of 10 mg/mL. The MBC values against MRSA ranged from 39.0 to 1.95 µg/mL, while against E. coli, the MBC values were slightly lower, ranging from 78.1 to 1.95 µg/mL. In conclusion, all chemical concentrations exhibited activity against the studied microorganisms, indicating their potential as antimicrobial agents.